Smart Hydrant Monitoring System Prototype - Helmut Antonio Saavedra García; Ernesto de Jesús Mendoza Vallecillo (Tecnología en Marcha)
In this article, we will develop a system that allows the monitoring of hydrants through an Arduino microcontroller in the city of Managua. Which will consist of 3 stages. A Stage of Sensors and Actuators, Communication Stage and Server Configuration. Which can be monitored from a subdomain of the Firebase platform.